An Applied Study to Improve the Sustainability of Buildings by Reducing Energy Consumption Costs Using Building Information Modeling (BIM) - ميا, رنا (Latakia University Journal -Engineering Sciences Series, 2023)
The issue of sustainability has become a global concern for many sectors as a result of the increasing negative impacts on the environment and society. In the construction sector, it has become necessary to take into account the issue of energy analysis and forecasting during the design of buildings, which is one of the most important elements of building sustainability. The research aims to study and apply a building information model to clarify the mechanism of the work of the BIM system with regard to the possibility of controlling energy costs during the life cycle of the building, before the start of implementation, and to determine the economic impact of some elements of sustainability. The design alternatives to building insulation and their impact on energy consumption were studied using the Revit and an energy analysis was done of the building using Green building studio to compare the performance of the isolated building and the traditional building. Various options were used to orient and isolate the building and thus compare the total costs of the project including construction and operation. Where it was concluded that BIM helps to implement energy analysis at a high speed and that the use of insulation materials according to specific options will allow to achieve significant savings that allow to reduce energy consumption and thus reduce the total costs of the building during the project life cycle stages to have more sustainable buildings.